A critical review of the literature on comfort of hearing protection devices: definition of comfort and identification of its main attributes for earplug types. (2nd December 2019) - Doutres, Olivier; Sgard, Franck; Terroir, Jonathan; Perrin, Nellie; Jolly, Caroline; Gauvin, Chantal; Negrini, Alessia
Abstract: Objective: This article presents a comprehensive literature review of past works addressing Hearing Protection Devices (HPD) comfort and to put them into perspective regarding a proposed holistic multidimensional construct of HPD comfort. Design: Literature review. Study samples: Documents were hand searched and Internet searched using "PubMed", "Web of Science", "Google Scholar", "ProQuest Dissertations and Theses Professional", "Scopus" or "Google" search engines. While comfort constructs and measurement methods are reviewed for both earplugs and earmuff types, results and analyses are provided for the earplug type only. Results: This article proposed a multidimensional construct of HPD comfort based on four dimensions: physical, functional, acoustical and psychological. Seen through the prism of the proposed holistic construct of HPD comfort, the main comfort attributes of earplugs have been identified for each comfort dimension. Conclusions: The observed lack of consensus on the definition of HPD comfort in the scientific community makes it difficult to prioritise the importance of comfort attributes yet necessary for future design of comfortable earplugs.